Brava gente brasileira e o “Brasil 500”: o espetáculo do descobrimento - Kátia da Costa Bezerra (Estudos de Literatura Brasileira Contemporânea)
Based on studies of Diana Taylor, Anthony Pagden and Jean Starobinski, this essay examines how the film Brava gente brasileira, dramatizes some of the conflicts present in the reenactment of the discovery during the celebrations of the “Brazil 500.” The purpose is to reflect on some of intertexts involved in the process of building a sense of Brazilianness.